IMPLEMENTASI SIKLUS AKUNTANSI PT. DIGITAL KALIBRASI HEBAT - Monika, Anne (Journal of Islamic Banking, Economics and Finance, 2025)
This study aims to determine the suitability of the application of accounting at PT. Digital Kalibrasi Hebat in Pekanbaru with generally accepted accounting principles. The data used in the study are primary data and secondary data. Data collection techniques are carried out by interviews, documentation and observation. The company's data analysis technique is then arranged in such a way and analyzed based on relevant theories, then a conclusion can be drawn. The results of the study concluded that the accounting basis used by PT. Digital Kalibrasi Hebat in determining income and expenses uses the accrual method, namely the recognition of the impact of transactions and other events at the time of the transaction and event. The company does not calculate and present the allowance for bad debts so that the value of receivables presented in the balance sheet is too large. The accounting process in brief. PT. Digital Kalibrasi Hebat does not comply with Generally Accepted Accounting Principles because PT. Digital Kalibrasi Hebat only maintains a general journal and does not maintain accounting books. In the fixed asset report, the company depreciates buildings, under normal conditions buildings and land should not experience depreciation but always experience an increase in value in accordance with market developments. The company has not presented a report on changes in equity in the financial statements. Application of accounting at PT. Great Calibration Digital is in compliance with Generally Accepted Accounting Principles.